Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Pada Materi Keterampilan Menulis Karangan Narasi Menggunakan Teknik Meneruskan Cerita Bagi Siswa Kelas XI SMK Negeri 2 Garut - Atin Priatin Nur Haeni (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
The skills of writing narrative essays for Class XI students of SMK Negeri 2 Garut are still low. Therefore, it is necessary to use learning techniques that can increase student motivation and achievement, namely by telling stories. The purpose of this study was to describe the improvement in writing narrative essay skills and changes in the behavior of Class XI students at SMK Negeri 2 Garut in writing narrative essays using the storytelling method. This type of research is classroom action research (CAR). Classroom action research was carried out in four stages, namely: (1) planning, (2) action, (3) observation or observation, and (4) reflection. This study uses two variables, namely the skill of writing narrative essays and the technique of telling stories. Data collection was divided into two stages, namely cycle I and cycle II using test and non-test techniques with the application of learning techniques. The tests used were action tests in the form of assignments to write narrative essays, while the non-test techniques used were observations, journals, interviews, and photo documentation. This study uses qualitative and quantitative data analysis techniques. The results of this study indicate an increase in narrative essay writing skills with storytelling techniques for Class XI students of SMKN 2 Garut. The average value in the first cycle stage is 67.8. in cycle II to 79.43. The results of non-test data analysis showed an increase in the behavior of Class XI students at SMKN 2 Garut in a positive direction. Students became more enthusiastic about learning to write news texts.